Research and publish, publish or perish, so what? - Mutune, Fellis N. (Machakos University Press, 2019)
Research primarily is geared towards creation of new knowledge. Researchers in Applied Linguistics are expected to identify and solve linguistic problems in the society. For this to be realized scholars in applied linguistics should engage in research that influences policy formulation or change of policy and also engage stakeholders at the formative stages of the research process .Over the years, scholars have pursued Applied Linguistics and explored varied issues in an endeavour to acquire certificates for different motivations. In each and every institution of higher learning in Kenya, there has been a research policy that at the undergraduate level, each and every student must come up with a project before graduation. The Commission of University Education has passed that at the post graduate level, a candidate pursuing masters should publish a paper from their research project or dissertation before graduation. At the PhD level, one has to publish two papers from their research work. Of what value are these research activities? As applied linguistics researchers we need to bring the policy actors and stakeholders on board. This paper explores platforms, strategies and opportunities which an applied linguist can maximize in engaging the policy actors. Further, the paper examines the tools and skills that an applied linguist should have for effective communication with various types of stakeholders to get value for the research conducted. Also, the paper explores the tools which an applied linguist can use for mapping policy actors. It is hoped that the issues addressed in this paper will be instrumental to an applied linguist on how to engage the stakeholders in the research process and also the implementation of the research findings to facilitate formulation of policies that bring change.
Keywords: Publish; perish; policy actors; stakeholders; Commission of Higher Education; Applied Linguistic